PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENJASORKES MELALUI METODE DRILL DI KELAS X.IIK.1 MAN 2 PASAMAN BARAT - IRFAN IRFAN (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes obtained by students in Class X.IIK.1 MAN 2 Pasaman Barat in Penjasorkes learning it was found that student learning outcomes in Penjasorkes learning are still very low and many are under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in Penjasorkes subjects through the application of learning methods through the application of the Drill Method in Class X.IIK.1 MAN 2 Pasaman Barat. This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 36 students of Class X.IIK.1 MAN 2 Pasaman Barat. Research data were collected using tests. Data were analyzed using percentages. Based on the results of research and discussion, it can be concluded that the drill method can improve student learning outcomes in learning Penjasorkes at MAN 2 Pasaman Barat. Student learning outcomes from cycle I to cycle II have increased. Student learning outcomes in the first cycle was 67.50 (enough) increased to 87.50 (good) with an increase of 20.00.